Proposed research for optimization of the performance of cooling system in data center facilities - Romadhon, Rahmat; Ali, Maisarah (2008)
The rapid growth in the information technology in many sectors and innovation in the supporting electronic component and data center equipment, has led the increasing demand of the data center providing and performance. The conditions directly implicate to the increasing of power consumption and heat load density. The cooling system takes critical mission to provide the environment of data center for the equipment working properly. Unfortunately, the power consumption of the cooling system increase along with the increasing of server density. Data center requires three to five times higher cooling capacity for the same space area than the cooling system for office building. Improvement in the cooling system of data center will give significant benefit to the energy efficiency. Heat dissipation from the component inside the equipment is the major heat load for the cooling system. Investigation of the effective cooling inside the equipment is an important part for the optimization of cooling system. In this paper, authors attempt to summarize the problem of energy usage in the cooling system of data center and interest to look for opportunity for energy efficiency.